Handbook of materials failure analysis : with case studies from the construction industry - Makhlouf, Abdel Salam Hamdy; Aliofkhazraei, Mahmood (Butterworth-Heinemann, an imprint of Elsevier, 2018)
Handbook of Materials Failure Analysis: With Case Studies from the Construction Industry provides a thorough understanding of the reasons materials fail in certain situations, covering important scenarios including material defects, mechanical failure due to various causes, and improper material selection and/or corrosive environment. The book begins with a general overview of materials failure analysis and its importance, and then logically proceeds from a discussion of the failure analysis process, types of failure analysis, and specific tools and techniques, to chapters on analysis of materials failure from various causes. Failure can occur for several reasons, including: materials defects-related failure, materials design-related failure, or corrosion-related failures. The suitability of the materials to work in a definite environment is an important issue. The results of these failures can be catastrophic in the worst case scenarios, causing loss of life. This important reference covers the most common types of materials failure, and provides possible solutions.